Visualization and quantitative evaluation of aerosol deposition using 3D-printed adult nose cavities - Wei He; Muhan Shi; Yaozhong Lu; Chengsheng Chu; Xiaolong Wang; Min Wang; Xiaofang Zhang (Heliyon)
Local steroid medication is one of the most important treatment options for chronic rhinosinusitis. Regional deposition has a higher clinical value compared with total deposition in predicting treatment outcomes or evaluating adverse reactions. The goal of this project is to propose an effective technique for visualizing and quantifying aerosol deposition in a three-dimensional adult nasal cavity, and to verify the practicality of this method. Three-dimensional (3D) nasal cavity models were constructed from computed tomography (CT) scans of one post-operative rhinosinusitis subject using imaging software. The nasal cast was coated with a water-indicating paste and deposited with saline; a liquid dressing was added to visualize the progress. The quantity of liquid dressing was evaluated via HPLC and the liquid deposition was analyzed within the nasal cast cavity. Herein, 98.77 % of the particles generated by the nebulizer were over 5 μm, suggesting that most of the aerosol could effectively enter the nasal cavity instead of the lower respiratory system. The liquid dressing was mainly deposited in the nasal cavity, ethmoid sinus, and frontal sinus according to the visualization tests. HPLC results suggested that the main deposits were the frontal sinus (up to 41.80 %) as well as in the sphenoid sinus and ethmoid sinus (14.00 %). The large particle nebulizer (BM-TCA) generally led to better deposition in sinus areas when compared to the smaller particle nebulizer (PARI). This technology allows for in vitro testing of various types of nasal preparations and equipment under various test methods.